Valence-State-Engineered Electrochemiluminescence from Au Nanoclusters - Wang, Dongyang; Gao, Xuwen; Jia, Jingna; Zhang, Bin; Zou, Guizheng (ACS nano, 2023)
To determine the intrinsic effects of body elements on the electrochemiluminescence (ECL) of metal nanoclusters (NCs), herein, a valence-state engineering strategy is developed to adjust the NCs’ ECL with bovine serum albumin (BSA)-stabilized AuNCs as a model, in which engineering the valence state of the Au body element, i.e., Au(0) and Au(I), is performed via successively reducing the precursor AuCl4 – to Au(I) and Au(0) with BSA. The obtained BSA-AuNCs/N2H4 system leads to three anodic ECL processes at 0.37 (ECL-1), 0.85 (ECL-2), and 1.45 V (ECL-3). ECL-1 is generated from the BSA-Au(0) section of BSA-AuNCs in a surface-defect-involved route and is much stronger and red-shifted compared to ECL-2 and ECL-3, which are generated from the BSA-Au(I) section of BSA-AuNCs in the band-gap-engineered route. Each of the anodic ECL processes can be selectively generated and/or suppressed via adjusting the Au(I)/Au(0) ratio of BSA-AuNCs, tunable ECL generation route, and triggering potential, and the emission intensity and waveband of metal NCs are conveniently achieved in body-element-involved valence-state engineering.